A Comparative Analysis of Takaful and Conventional Insurance Models: Principles, Practices, and Performance - Dr. Arif Hussain; Syed Ali Abbas Abidi; Dr. Abdul Ghani (Journal of Religion and Society, 2025)
This study provides a comprehensive comparison of Takaful and conventional insurance models, examining their underlying principles, operational practices, and financial performance. Takaful, an Islamic insurance concept based on mutual cooperation (taʿāwun) and risk-sharing (tabādur al-mukhāṭarah), has gained significant attention in recent years. In contrast, conventional insurance models are based on commercial principles, often involving risk transfer and profit maximization. The study employs a mixed-methods approach, combining qualitative and quantitative analyses to compare the two models. The results show that Takaful's cooperative structure and Sharīʿah-compliant principles offer distinct advantages, including enhanced financial inclusion, social responsibility, and risk management. However, Takaful faces challenges in terms of scalability, regulatory frameworks, and product innovation. The comparative analysis reveals significant differences in the financial performance of Takaful and conventional insurance models. Takaful operators (mudabbirīn al-Takaful) demonstrate stronger solvency ratios and more stable financial performance, while conventional insurers exhibit higher profitability and market penetration. The study also explores customer perceptions and satisfaction levels, highlighting the importance of Sharīʿah compliance and social responsibility in Takaful's appeal. This research contributes to the existing literature on Islamic finance (al-mālīyyah al-Islāmiyyah) and insurance (al-taʾmīn), offering insights for policymakers, insurers, and customers. The findings suggest that Takaful can be a viable alternative to conventional insurance, particularly for Muslim customers seeking Sharīʿah-compliant financial products. However, further research is needed to address the challenges facing Takaful operators and to explore opportunities for innovation and growth.The study's conclusions have implications for the development of Takaful and conventional insurance models, highlighting the need for greater collaboration, innovation, and regulatory clarity. By exploring the strengths and weaknesses of both models, this research aims to inform the development of more effective and sustainable insurance solutions. Keywords: Takaful, Conventional Insurance, Islamic Finance.